(untitled) (ІННОВАЦІЙНА ЕКОНОМІКА, 2024)
Тимощук В.В. ТРАНСФОРМАЦІЯ ІНСТИТУЦІОНАЛЬНОГО СЕРЕДОВИЩА ІННОВАЦІЙНОГО РОЗВИТКУ СУСПІЛЬНОГО ГОСПОДАРСТВА Мета. Узагальнення тенденцій трансформації інституціонального середовища інноваційного розвитку національної економіки та особливостей інституціонального забезпечення розвитку інновацій. Методика дослідження. Теоретико-методологічною основою дослідження є: системний підхід до узагальнення тенденцій трансформації інституціонального середовища інноваційного розвитку; інституціональний підхід до обґрунтування елементів регулюючих впливів формальних норм, орієнтованих на розвиток інновацій; структурно-функціональний аналіз ‒ для визначення макроекономічного та мікроекономічного прояву постіндустріальних трансформацій на інституціональне середовище. Результати дослідження. Акцентовано, що для формування дієвого інструментарію інноваційної модернізації національного господарства важливо врахувати глобальні фактори економічної динаміки, їх екзогенні та ендогенні прояви. Констатовано, що сучасним вектором глобальних трансформацій, що вже справляє вплив на національну економіку, стала цифрова модернізація, яка кардинально змінює економічні взаємовідносини людей та фундаментальну роль економічних ресурсів. Аргументовано, що цифровізація породжує ефекти, які отримують макроекономічний прояв за допомогою появи й поширення нових бізнес-стратегій, змін ринкових умов, підвищення рівня продуктивності праці. На мікроекономічному рівні цифровізація призводить до зміни структури й пропозиції виробництва товарів, їх якості, логістичних й реалізаційних умов та взаємодії виробників. Цифрові технології сприяють появі нових інституцій і інститутів та впливають на діючі за допомогою алгоритмізації інституціонального впливу й регулювання, мінімізації впливу інституціональних пасток і попередження появи нових, зниження стійкості наявних рутин, підвищення чи зниження ефективності інститутів. Наукова новизна результатів дослідження. Обґрунтовано, що постіндустріальні трансформації економіки та інституціонального середовища змінюють структурну характеристику, але не сутнісне призначення інституцій та інститутів в інноваційному розвитку. Процеси цифровізації і мережевих взаємодій сприяють стандартизації й алгоритмізації інститутів, запровадженню «цифрових інститутів»; підвищують ефективність сформованих інститутів та інституцій; утворюють нові дисфункцій через опортуністичну поведінку економічних суб’єктів; формують інституціональний «вакуум» через поширення цифрових технологій, які ще не стали вбудованими у інституціональне середовище. З огляду на завдання інноваційної модернізації суспільного господарства, для виключення негативного впливу необхідно модернізувати і саме інституціональне середовище для зміни спрямованості функціонального впливу регулюючих норм та впровадження організаційних інновацій, що здатні поліпшувати інституціональну структуру. Практична значущість результатів дослідження. Теоретичні й методологічні положення дослідження поглиблюють практичні засади й інструментарій інституціонального регулювання інноваційної модернізації національної економіки. Ключові слова: модернізація, інноваційний розвиток, суспільне господарство, трансформація, інституціональне регулювання, інститут, інституція. Tymoshchuk V.V. TRANSFORMATION OF THE INSTITUTIONAL ENVIRONMENT OF INNOVATIVE DEVELOPMENT OF THE PUBLIC ECONOMY Purpose. The aim of the article is to generalize the trends of the transformation of the institutional environment of the innovative development of the national economy and the features of the institutional support for the development of innovations. Methodology of research. The theoretical and methodological basis of the research is: a systematic approach to the generalization of trends in the transformation of the institutional environment of innovative development; institutional approach to the substantiation of the elements of the regulatory influence of formal norms, oriented towards the development of innovations; structural and functional analysis – to determine the macroeconomic and microeconomic manifestation of post-industrial transformations on the institutional environment. Findings. It is emphasized that for the formation of an effective toolkit for innovative modernization of the national economy, it is important to take into account global factors of economic dynamics, their exogenous and endogenous manifestations. It was established that the modern vector of global transformations, which is already having an impact on the national economy, has become digital modernization, which radically changes the economic relationships of people and the fundamental role of economic resources. It is argued that digitalization generates effects that receive macroeconomic manifestation through the emergence and spread of new business strategies, changes in market conditions, and an increase in labour productivity. At the microeconomic level digitalization leads to a change in the structure and supply of goods production, their quality, logistics and sales conditions, and the interaction of manufacturers. Digital technologies contribute to the emergence of new institutions and institutes and influence existing ones by algorithmizing institutional influence and regulation, minimizing the impact of institutional traps and preventing the emergence of new ones, reducing the stability of existing routines, increasing or decreasing the effectiveness of institutions. Originality. It is substantiated that the post-industrial transformations of the economy and the institutional environment change the structural characteristics, but not the essential purpose of institutions and institutes in innovative development. The processes of digitalization and network interactions contribute to the standardization and algorithmization of institutes, the introduction of "digital institutes"; increase the efficiency of established institutes and institutions; create new dysfunctions due to the opportunistic behaviour of economic subjects; form an institutional "vacuum" due to the proliferation of digital technologies that have not yet become embedded in the institutional environment. In view of the task of innovative modernization of the public economy, in order to exclude the negative impact it is necessary to modernize the institutional environment itself to change the direction of the functional influence of regulatory norms and introduce organizational innovations that can improve the institutional structure. Practical value. The theoretical and methodological provisions of the study deepen the practical principles and tools of institutional regulation of innovative modernization of the national economy. Key words: modernization, innovative development, social economy, transformation, institutional regulation, institute, institution.